PENINGKATAN STATUS GIZI BALITA MELALUI PENGEMBANGAN DAN PRODUKSI ABON IKAN NILA DI DESA PEMATANG JERING KECAMATAN JAMBI LUAR KOTA TAHUN 2023 - Asparian, Asparian; Aprilianti, Dewi; Qalbi, Nurul; Azizah, Fitri; Sofira, Mawar Dia (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Toddlers are one of the risk groups for experiencing a lack of nutritional intake, which affects their nutritional status. According to the results of SSG1 2022, it is stated that the prevalence of underweight or malnourished children under five (weight according to age) in Jambi Province is 13.8% and in Muaro Jambi Regency is 16.2%. In Pematang Jering Village itself, there are still health problems among children, including malnutrition, stunting and wasting. Malnutrition is a condition where the body's nutritional needs are not met within a certain period of time so that the body breaks down food reserves under the fat layer and layers of the body's organs. Maternal parenting patterns show that mothers with poor parenting patterns have a greater chance of having children who experience malnutrition problems than mothers with good parenting patterns. Good parenting consists of providing IMD, giving breast milk and MP-ASI as well as practicing hygiene or environmental sanitation. Pematang Jering Village has a Polindes (Village Maternity Center). This Polindes is used once a month for the implementation of posyandu. The results of data measuring height according to age (TB/U) carried out by the Posyandu in Pematang Jering Village, out of a total of 105 children in Pematang Jering Village, found that 25 children had undernutrition problems that did not meet the ideal standards according to age. The methods used were Focus Group Discussion (FGD), Introduction of Alternative Innovations for Toddler MPASI, Education on Tilapia Floss Production, Formation of Cadres and Structures, Monitoring of Shredded Production, Monitoring and Evaluation of the pre-test and post-test results, namely 16.66% to 83, 33% of mothers of toddlers have an understanding regarding providing MP-ASI food and producing shredded Nilla fish properly and correctly.